PENGARUH KUALITAS PELAYANAN JASA TERHADAP KEPUASAN PELANGGAN GOLONGAN RUMAH TANGGA KECAMATAN BUKIT KECIL (Studi pada Pelanggan PT PLN (Persero) Cabang Palembang Rayon Rivai) - Dibyantoro Dibyantoro; Mariskha Z; Yunita Kusumawardhani (Politeknik Negeri Sriwijaya, 2013)
The object of this final report is to find out the influence of service quality to the customer satisfaction of PT PLN (Persero) Cabang Palembang Rayon Rivai. The purpose of this final report is to investigate the influence of service quality which is most dominantly influence the customer satisfaction and to investigate the quality that is given whether it is already fulfilled the customer satisfaction. The data are got questioner, observation, interview, the data are analyzed by using the theories from Nasution (2003), Lupiyoadi (2001), Umar (2002), Tjiptono (1999), and by using the SPSS analysis for windows 11.5 version Multiple Regression formula. The result shows that R Square is the colleration service quality and the customer perception satisfaction which were 30.6%, while the remaining 69.4% were influenced by other factor not included in this study. The factor of Tangibles more influence customer satisfaction. Writer suggests that PT PLN (Persero) Cabang Palembang Rayon Rivai should increase the service quality in Responsiveness dimention, because this dimention is that costumer want.